Terminating Cover Crops Effectively for Weed Suppression - Pratap Devkota; Michael J. Mulvaney; David L. Wright (EDIS, 2021)
When utilizing cover crops for weed suppression, one important consideration is effective termination before planting the main crop. A major issue with improper termination is that the cover crop can become problematic and compete with the main crop, like other weeds. However, proper planning of the termination timing and method can minimize these issues and maximize the benefits of cover crop use. This 5-page publication discusses herbicide application, roller-crimper termination, tillage, and appropriate growth stages for termination. Written by Pratap Devkota, Michael J. Mulvaney, and David Wright, and published by the UF/IFAS Agronomy Department, February 2021.